2022
DOI: 10.31083/j.fbl2705146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of New Drugs for Therapeutic Intervention in Alzheimer’s Disease

Abstract: The increases in population ageing and growth are leading to a boosting in the number of people living with dementia, Alzheimer's disease (AD) being the most common cause. In spite of decades of intensive research, no cure for AD has been found yet. However, some treatments that may change disease progression and help control symptoms have been proposed. Beyond the classical hypotheses of AD etiopathogenesis, i.e., amyloid beta peptide (Aβ) accumulation and tau hyperphosphorylation, a trend in attributing a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 149 publications
1
11
0
Order By: Relevance
“…Donanemab, another humanized mAb from Eli Lilly & Co., recognizing Aβ(p3-42) a pyroglutamate form of Aβ that is aggregated in amyloid plaques [ 63 , 64 , 65 ]. This humanized IgG1 antibody is currently being tested on AD patients with prodromal to moderate AD in a phase III clinical trial [ 66 , 67 ].…”
Section: Current Treatment Strategies Targeting Aβmentioning
confidence: 99%
“…Donanemab, another humanized mAb from Eli Lilly & Co., recognizing Aβ(p3-42) a pyroglutamate form of Aβ that is aggregated in amyloid plaques [ 63 , 64 , 65 ]. This humanized IgG1 antibody is currently being tested on AD patients with prodromal to moderate AD in a phase III clinical trial [ 66 , 67 ].…”
Section: Current Treatment Strategies Targeting Aβmentioning
confidence: 99%
“…Baik and colleagues demonstrated that in an LPS-induced mouse model of cognitive decline, LPS robustly enhances mTOR and HIF1α transcription [ 144 ]. Activated mammalian targets of rapamycin complex 1 (mTORC1) strongly hamper autophagy through phosphorylation of p70S6K [ 145 ].…”
Section: Microglia Impairment Heralds Brain Connectivity Dysfunctionmentioning
confidence: 99%
“…For a long time, the FDA has approved only four drugs for the treatment of AD. These medications consist of three cholinesterase inhibitors (donepezil, galantamine, and rivastigmine) and an N-methyl-D-aspartate receptor antagonist (memantine) [32]. In recent years, Chinese-approved sodium oligomannate and FDA-approved adacunumab were used to slow the progression of AD [32].…”
Section: Introductionmentioning
confidence: 99%